2015
DOI: 10.1002/acr.22519
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of Tumor Necrosis Factor Inhibitors and Glucocorticoids on Bone Density in Rheumatoid Arthritis and Ankylosing Spondylitis Trials

Abstract: Objective. To examine the impact of antirheumatic drugs on bone mineral density (BMD) in rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PsA), and psoriasis using a systematic review. Methods. Electronic databases were systematically searched for randomized controlled trials. Studies were grouped based on disease, treatment, and site of BMD measurement. Change in BMD (DBMD) from baseline to end of study was recorded. Standardized mean difference (SMD) of DBMD between treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 30 publications
1
32
0
4
Order By: Relevance
“…In RA, our metaanalysis of randomized controlled trials that studied the effects of CS on bone loss showed an association between oral CS use and lumbar spine bone loss (mean difference in DBMD -0.3, 95% CI -0.55 --0.04) 96 . Included studies used an average daily dose of prednisone or prednisolone ranging from 6 mg to 12 mg for a study period ranging from 20 weeks up to 2 years.…”
Section: Methodsmentioning
confidence: 89%
“…In RA, our metaanalysis of randomized controlled trials that studied the effects of CS on bone loss showed an association between oral CS use and lumbar spine bone loss (mean difference in DBMD -0.3, 95% CI -0.55 --0.04) 96 . Included studies used an average daily dose of prednisone or prednisolone ranging from 6 mg to 12 mg for a study period ranging from 20 weeks up to 2 years.…”
Section: Methodsmentioning
confidence: 89%
“…The large amount of data and evidence. Some clinical questions and recommendations had enough data and evidence in the literature to warrant separate publication and discussion; these have been published in peer-reviewed journals and presented at international conferences 3,4,5,6,7 . Other questions, which lacked data or evidence in the literature, could not lead to separate publications; these limitations were mentioned in our discussion.…”
Section: To the Editormentioning
confidence: 99%
“…По данным ме-таанализа S. Siu и соавт. [94] (5 РПКИ), при РА лечение ГК ассоциируется с уменьшением потери МПК в зоне луче-вой кости, не влияет на МПК бедра, но приводит к сниже-нию МПК поясничного отдела позвоночника (p=0,02 по сравнению с пациентами, не получавшими ГК). Однако при раннем РА ГК не оказывают негативного влияния на МПК бедра и позвоночника.…”
Section: безопасностьunclassified